How engineering consultants should communicate with their clients: an Integrated Marketing Communications (IMC) perspective. Issue 1 (1st January 2017) - Watson, Neil
Abstract: As engineering consultancy service quality offerings approach levels of parity in the market place, establishing an effective communication strategy is increasingly becoming the fundamental marketing function that can create and maintain service differentiation and brand equity, leading to a sustainable competitive advantage. However, certain cultural and attitudinal barriers, borne out of perceptions, exist that inhibit marketing practices within this industry. This research was undertaken to challenge these perceptions, evaluate the scope for improvement in communications and examine how an integrated marketing communication strategy can improve the consultant's competitive advantage within a business-to-business context. In addition to an extensive review of extant academic literature relevant to the industry, this study used survey-questionaries to examine client-perceptions of the marketing communication channels available to engineering consultants. Furthermore, using a subjective review of consultant websites as a proxy, it assessed the level of alignment between existing consultant communication strategies and the previously established client-perceptions.